UNJUK KERJA KOLEKTOR TABUNG PEMANAS AIR PADA SAAT CHARGING MENGGUNAKAN PHASE CHANGE MATERIAL (PCM) DENGAN DAN TANPA REFLEKTOR - Mahros Darsin; Khamdan Khavivi; Digdo Listyadi Setyawan (Universitas Muhammadiyah Ponorogo, 2020)
In solar powered water heaters, solar radiation falls into and then absorbed by tube collectors which are then used as a source of water heaters for household and industrial needs. One effort to improve efficiency in solar-powered water heater systems is by adding a reflector under the collector. The main purpose of this study is to find out the effect of the reflector on the collector's efficiency during the charging period. The tube collector consists of absorber pipes, water pipes, and reflector. While the parabolic reflector is made of stainless to maximize reflection to the collector. In these experiments, the water flow was varied at 0.48 l/min, 0.59 l/min, and 1.82 l/min. Temperature measurements were carried out at several points: (i) inlet, (ii) outlet and (iii) phase change material (PCM). While radiation intensity was measured using a pyranometer. The data were compared between heater with and without the reflector. The highest collector efficiency was achieved when applying 1.82 l/minute with the maximum collector performance with reflector and without a reflector is 76.8% and 69.7% respectively. It is be concluded that the use of reflectors can increase the efficiency of tube collectors for water heaters. The outlet temperature was higher by 1.7% than the previous result when using water flow rate of 0.59 l/min.